The Copyright Law Framework and Its Interaction with Open Access Repositories in Europe - Koutras, Nikos (2018)
The paper examines the European copyright framework and its interaction with open access repositories. Access to information resources has become a modern necessity that needs to be met to share equitably the wealth of the European society. The Directives with intellectual property provisions to enhance copyright law policy makers are the foundation of the European copyright regime. This statement helps me to clarify the design and assumptions underlying open access practice in Europe. The paper analyses strengths and short-comings of these Directives in relation to copyright protection and open access practice among European member states.